Living without enemies : being present in the midst of violence - Wells, Samuel, 1965-; Owen, Marcia A., 1955- (Downers Grove, IL : IVP Books, 2011)
Marcia Owen and Samuel Wells tell the story of a community's journey into deeper dimensions of social engagement. Through prayer vigils for local victims of gun violence and friendships with both victims and offenders, Owen learned that presence was precisely the opposite of violence -- it was love. Living Without Enemies offers profound insights into what it takes to overcome powerlessness, transcend fear and engage in radical acceptance in our dangerous world.
Nazareth -- Ministry -- Silence -- Touch -- Words -- Kingdom.
Includes bibliographical references (p. 140)
Keywords: Nonviolence -- Religious aspects -- Christianity; Love -- Religious aspects -- Christianity; Church work; Violence -- North Carolina -- Durham; Violence -- North Carolina -- Durham -- Prevention